A Study on Doping Punishment by the Criminal Law in China and Foreign Countries - Jianhui Cai (Forest Chemicals Review, 1970)
In this paper, the penal provisions on doping control in foreign countries are studied by literature review. In addition, the main causes for the accusation of crimes involving doping in Italy, Germany, the United States, Spain, France and other countries are discussed: (1) Fraud; (2) Perjury; (3) Producing, supplying, owning, importing and exporting illegal drugs without permission; Consumption of controlled goods; (4) Purchasing, managing and instigating the use of doping products; Blood doping; (5) Intentional injury; (6) Use of doping. According to these causes, the foreign punishment on doping is mainly used to punish the participants in the production and trading of doping. It is also found that athletes who take prohibited stimulants will be charged with crimes in Italy and other countries, but still with some difficulties. Based on the study of the attitudes of the WADA and the United Kingdom and other countries that disapprove of the criminal law legislation specifically for anti-doping, combined with the difficulties faced by the criminal conviction of anti-doping and the actual situation of limited law enforcement resources in China, it is considered that China can expand the content of "drugs" in the criminal law by amending the criminal law or issuing judicial interpretations, so as to better play the role of anti-doping. Finally, it is suggested that the definition of "drug" in criminal law should be explained to facilitate the practical operation of anti-doping, and the anti-doping publicity and education for athletes should be strengthened.